Chasing Vermeer - Balliett, Blue; Helquist, Brett (New York : Scholastic Press, 2004)
When strange and seemingly unrelated events start to happen and a precious Vermeer painting disappears, eleven-year-olds Petra and Calder combine their talents to solve an international art scandal.
Keywords: Vermeer, Johannes; Art; Mystery and detective stories